DEVELOPING AND TESTING A SMART AND PRECISE SYSTEM FOR PLANT FERTILIZATION - Tahseen Allawi Al-Shajari, Tahseen Allawi Al-Shajari; Alaa Kameel Subr, Alaa Kameel Subr (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The objective of this study was to increase nutrient efficiency and decrease the detrimental effects on the environment. Using automation, sensing technologies and data analysis to control the optimum distribution of fertilizers and water based on real-time crop requirements. So, sensors to determine soil nutrients (nitrogen, phosphorus and potassium), as well as specific parameters like pH, moisture content and temperature were developed to create a smart system. Upon detection of nutrient deficiency, fertilizers are applied automatically or remotely using the Internet. It was conducted using three fertilization systems (automated, semi-automated and traditional) and three different types of drippers (GR, T-TAPE, EOLOS D2000).Results showed that the automated system achieved the highest crop yield (20.71 tons/hectare) and the lowest fertilizer consumption (86.67 kg) compared to the traditional system (17.39 tons/hectare and 158.96 kg). Nutrient levels in the soil also improved, enhancing soil fertility. The findings confirm that smart fertilization enhances crop productivity, reduces fertilizer waste, and improves soil fertility, making it a sustainable and efficient option for modern agriculture.